2018
DOI: 10.1002/pbc.27009
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐escalation is needed for gross disease in high‐risk neuroblastoma

Abstract: After subtotal resection, patients who received less than 30 Gy had poor local control. Doses of 30-36 Gy are likely needed for optimal control of gross residual disease at the time of consolidative RT in high-risk neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…There has been speculation whether the presence of gross disease after surgery can be controlled by a higher dose of radiation (36 Gy) as employed in the NB97 trial . A recent publication reviewed the published locoregional control rates after standard dose radiation (21–24 Gy) versus higher dose radiation (30–36 Gy); in children with STR, local failure was found in 17% to 43% of patients receiving standard and 0% in those receiving higher dose RT . We did not find a difference in locoregional control, progression‐free, or OS according to the degree of resection.…”
Section: Discussionmentioning
confidence: 55%
“…There has been speculation whether the presence of gross disease after surgery can be controlled by a higher dose of radiation (36 Gy) as employed in the NB97 trial . A recent publication reviewed the published locoregional control rates after standard dose radiation (21–24 Gy) versus higher dose radiation (30–36 Gy); in children with STR, local failure was found in 17% to 43% of patients receiving standard and 0% in those receiving higher dose RT . We did not find a difference in locoregional control, progression‐free, or OS according to the degree of resection.…”
Section: Discussionmentioning
confidence: 55%
“…In Europe, there is a debate, if, after subtotal resection a dose increase with 36 Gy may be advantageous. A retrospective study from the Memorial Sloan Kettering Cancer Centre showed that patients with residual tumor who had received a dose of more than 30 Gy remained free of local failure (100%), while 30% of those who were irradiated with a dose below 30 Gy experienced local failure (44). Simon et al had comparable results for patients with residual tumor who received a dose of 36-40 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies reported that a higher dose is needed to control gross residual tumor after incomplete surgery [17,18], the optimal dose of RT is still unclear. In this study, 2 patients received boost RT for gross residual tumor with a total radiation dose of 27 and 36 Gy, respectively.…”
Section: Discussionmentioning
confidence: 99%